Evaluating the Effect of Beauty on Labor Market Outcomes: A Review of the Literature - Xing (Michelle) Liu; Eva Sierminska (Institute for the Study of Labor (IZA), 2014)
An important underlying determinant of wage discrimination, as well as the gender wage gap is the way the labor market rewards individual physical attractiveness. This article surveys the extensive empirical literature of the effect of physical attractiveness on labor market outcomes. Particular attention is given to the channels through which attractiveness may affect individual labor market outcomes and the way attractiveness affects gender wage differentials. Further research is needed on the effect of attractiveness within occupations in order to provide more evidence on its productivity-enhancing channel of transmission and the effect this has on the gender wage gap.
Keywords: J71; J31; J2; J16; 330; beauty premium; cross-country; discrimination; gender differentials; human capital model; occupational sorting; physical attractiveness; productivity; stereotypes; wages; wage discrimination